A CH4 / CO2 dry reforming CoNi bimetallic catalyst, preparation method and application
The preparation of CoNi bimetallic catalysts by hydrothermal method solves the problems of resource shortage and poor stability of existing catalysts in industrial applications, and achieves low-temperature and efficient catalysis of CH4/CO2 dry reforming reaction, with significant activity improvement and stability optimization.
Patent Information
- Application Number
- CN202411045285.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-01
AI Technical Summary
The existing catalysts used in the dry reforming of CH4/CO2 have problems such as shortage of resources, poor high temperature resistance, easy poisoning and poor use stability, which limits their widespread use in industrial applications.
The CoNi bimetallic catalyst is prepared by hydrothermal method. By mixing cobalt nitrate, nickel nitrate and aluminum nitrate with alkaline substances, and through hydrothermal reaction, drying, calcining and reduction, a CoNi bimetallic catalyst with high catalytic activity and stability is prepared.
It has achieved efficient catalysis of the dry reforming reaction of CH4/CO2 under low temperature conditions, and the activity of the catalyst has been significantly improved, with a conversion rate of 89.24% and 57.62%. It has excellent use stability and is suitable for industrial production.
Smart Images

Figure CN118976497B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic material synthesis, and in particular relates to a low-temperature and high-efficiency CH4 / CO2 dry reforming CoNi bimetallic catalyst, a preparation method and application thereof in low-temperature and high-efficiency CH4 / CO2 dry reforming. Background Art
[0002] The emission of greenhouse gas CO2 has increased with the sharp increase in fossil fuel consumption, which has brought great harm to the ecological environment. For this reason, the world is committed to reducing greenhouse gas emissions and trying to convert it into other high-value chemicals to achieve a green carbon cycle.
[0003] CH4 / CO2 dry reforming reaction can effectively convert CO2 and CH4 into synthesis gas (H2 / CO) (CH4+CO2=2CO+2H2, ΔH 298K = 247 kJ / mol), is a very promising application technology. This technology can not only utilize and convert CO2 and CH4 at the same time, but also reduce energy consumption while alleviating the pressure of greenhouse gas emissions, which is conducive to the realization of the "dual carbon" goals of countries around the world. In addition, the H2 / CO ratio of the reaction product is close to 1.0, which can be used as a raw material for carbonyl synthesis and FT synthesis. Under appropriate catalysts and conditions, liquid hydrocarbons and hydrocarbons can be synthesized to obtain important chemical products, realizing efficient conversion and resource utilization of greenhouse gases.
[0004] At present, the catalysts used for CH4 / CO2 dry reforming mainly use Group VIII transition metals as active components. Among them, precious metal catalysts (Pt, Pd, Rh, Ru and Ir, etc.) show high catalytic activity in reforming reactions, but their large-scale industrial application is limited due to their shortage of resources, poor high temperature resistance, easy poisoning and poor stability. With the development and innovation of catalysis and materials, researchers have found that non-precious metal catalysts can also show catalytic performance comparable to precious metals. Summary of the invention
[0005] Among many non-precious metal catalysts, Ni-based catalysts have good CH4 / CO2 dry reforming performance. Ni-based catalysts cannot meet the needs of industrial applications due to the weakness of active site sintering and rapid deactivation due to carbon deposition. Although the catalytic activity of Co-based catalysts is not as good as Ni, it is not easy to deposit carbon and has good stability.
[0006] The purpose of the present invention is to provide a low-temperature and high-efficiency CH4 / CO2 dry reforming CoNi bimetallic catalyst, a preparation method and an application thereof. The preparation method is simple and low-cost, and the prepared catalyst has high CH4 / CO2 dry reforming catalytic activity and high stability in use.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a CH4 / CO2 dry reforming CoNi bimetallic catalyst, comprising:
[0009] mixing cobalt nitrate, nickel nitrate and aluminum nitrate with distilled water to obtain a mixed metal salt solution;
[0010] Dissolve Na2CO3 and NaOH in distilled water to obtain Na2CO3 solution and alkaline solution;
[0011] Adding the mixed metal salt solution and the alkaline solution dropwise to the Na2CO3 solution simultaneously to obtain a mixed solution;
[0012] The mixed solution is stirred and then subjected to a hydrothermal reaction to obtain a precipitate;
[0013] The obtained precipitate is dried and then calcined in an air atmosphere to obtain a hydrotalcite-like oxide precursor;
[0014] The hydrotalcite-like oxide precursor is reduced in a hydrogen atmosphere to obtain a CoNi bimetallic catalyst.
[0015] Furthermore, the molar ratio of cobalt nitrate, nickel nitrate and aluminum nitrate is 0.5:0.3 to 1:1.
[0016] Furthermore, the molar ratio of Na2CO3 to aluminum nitrate is 2:1, and the molar ratio of NaOH to the sum of cobalt nitrate, nickel nitrate and aluminum nitrate is 2:1.
[0017] Furthermore, the stirring temperature of the mixed solution is 30-60° C., and the stirring time is 1.0-3.0 h.
[0018] Furthermore, the temperature of the hydrothermal reaction is 90-120° C., and the time of the hydrothermal reaction is 10.0-24.0 h.
[0019] Furthermore, the drying temperature of the obtained precipitate is 60-120°C.
[0020] Furthermore, the calcination temperature in air atmosphere is 400-600° C., and the calcination time is 3.0 h.
[0021] Furthermore, the reduction temperature under hydrogen atmosphere is 400-600° C., and the reduction time is 1.0-2.0 h.
[0022] In a second aspect, the present invention provides a CoNi bimetallic catalyst for CH4 / CO2 dry reforming prepared according to the aforementioned preparation method.
[0023] In a third aspect, the present invention provides the use of the aforementioned CoNi bimetallic catalyst in a CH4 / CO2 dry reforming reaction.
[0024] Furthermore, the temperature of the CH4 / CO2 dry reforming reaction is 500-700°C.
[0025] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0026] 1. The CoNi bimetallic catalyst prepared by the hydrothermal method of the present invention has a layered structure of a hydrotalcite-like precursor that promotes the high dispersion of Co in the catalyst. 0 and Ni 0 The formation of active centers is beneficial to the adsorption and activation of reactant molecules CH4 and CO2 to form active CH x (x < 4) and CO2 δ- Species can further promote the CH4 / CO2 dry reforming reaction. At the same time, the synergistic effect of Co species and Ni species can effectively improve the catalytic performance of CoNi bimetallic catalysts.
[0027] 2. The CoNi bimetallic catalyst prepared by the hydrothermal method of the present invention is used for CH4 / CO2 dry reforming reaction. The catalytic activity of the catalyst is significantly improved compared with that of the single Co catalyst. At normal pressure and reaction temperature of 700°C, the conversion rates of CH4 and CO2 reach 89.24% and 57.62%, respectively. After 10 cycles of testing, Ni 0.5 Co 0.5 The Al1-LD catalyst still maintains a relatively high CH4 / CO2 dry reforming catalytic performance and has excellent operational stability.
[0028] 3. The CoNi bimetallic catalyst was prepared by the hydrothermal method. The preparation method has simple process and low cost. It has high catalytic activity for CH4 / CO2 dry reforming reaction. It can also be used for RWGS and other reactions and is suitable for industrial production.
[0029] 4. The catalyst prepared by the present invention not only effectively improves the low-temperature performance of the Co-based catalyst, but also promotes the adsorption and activation of CH4 and CO2, effectively improving the catalytic performance of the CoNi bimetallic catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The catalyst precursor Ni prepared in Examples 1-3 and Comparative Examples of the present invention is 0.5 Co 0.5 Al1-LDO、Ni 0.3 Co 0.5 Al1-LDO、Ni1Co 0.5 Al1-LDO、Co0.5 H2-TPR image of Al1-LDO;
[0031] Figure 2 The catalyst precursor Ni prepared in Examples 1-3 and Comparative Examples of the present invention is 0.5 Co 0.5 Al1-LDH、Ni 0.3 Co 0.5 Al1-LDH、Ni1Co 0.5 Al1-LDH、Co 0.5 XRD pattern of Al1-LDH;
[0032] Figure 3 The catalyst Ni prepared in Examples 1-3 and Comparative Examples of the present invention 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD、Ni1Co 0.5 Al1-LD, Co 0.5 XRD pattern of Al1-LD;
[0033] Figure 4 The catalyst Ni prepared in Examples 1-3 and Comparative Examples of the present invention 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD、Ni1Co 0.5 Al1-LD, Co 0.5 TEM characterization test image of Al1-LD;
[0034] Figure 5 The catalyst Ni prepared in Examples 1-3 and Comparative Examples of the present invention 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD、Ni1Co 0.5 Al1-LD, Co 0.5 CO2-TPD diagram of Al1-LD;
[0035] Figure 6 The catalyst Ni prepared in Example 1 of the present invention 0.5 Co 0.5 The test graph of CH4 conversion rate in the catalytic CH4 / CO2 dry reforming reaction after Al1-LD was used 10 times in a cycle;
[0036] Figure 7 The catalyst Ni prepared in Example 1 of the present invention 0.5 Co 0.5The test graph of CO2 conversion rate in the catalytic CH4 / CO2 dry reforming reaction after Al1-LD was used 10 times in a cycle;
[0037] Figure 8 The catalyst Ni prepared in Example 2 of the present invention 0.3 Co 0.5 The test graph of CH4 conversion rate in the catalytic CH4 / CO2 dry reforming reaction after Al1-LD was used 10 times in a cycle;
[0038] Fig. 9 The catalyst Ni prepared in Example 2 of the present invention 0.3 Co 0.5 The test graph of CO2 conversion rate in the catalytic CH4 / CO2 dry reforming reaction after Al1-LD was used 10 times in a cycle;
[0039] Fig.10 The catalyst Ni1Co prepared in Example 3 of the present invention 0.5 The test graph of CH4 conversion rate in the catalytic CH4 / CO2 dry reforming reaction after Al1-LD was used 10 times in a cycle;
[0040] Fig.11 The catalyst Ni1Co prepared in Example 3 of the present invention 0.5 Test chart of CO2 conversion rate in catalytic CH4 / CO2 dry reforming reaction after Al1-LD was used 10 times in cycles. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention.
[0042] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.
[0043] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources. Example
[0044] A method for preparing a CH4 / CO2 dry reforming CoNi bimetallic catalyst specifically comprises the following steps:
[0045] (1) according to the molar ratio of cobalt nitrate, nickel nitrate and aluminum nitrate being 0.5:0.5:1, 0.7275 g of cobalt nitrate, 0.7269 g of nickel nitrate and 1.875 g of aluminum nitrate were weighed, and the weighed cobalt nitrate, nickel nitrate and nitric acid were mixed with distilled water to completely dissolve them, thereby obtaining a mixed metal salt solution;
[0046] (2) 1.06 g Na2CO3 [n(CO3 2- ) = 2n(Al 3+ )], 0.8 g NaOH [n(OH - ) = 2[n(Co 2+ )+n(Ni 2+ )+n(Al 3+ )] are dissolved in distilled water respectively, and after they are fully dissolved, a Na2CO3 solution and an alkali solution are obtained;
[0047] (3) simultaneously adding dropwise the mixed metal salt solution obtained in step (1) and the alkaline solution obtained in step (2) to the Na2CO3 solution obtained in step (2) to obtain a mixed solution;
[0048] (4) The mixed solution obtained in step (3) was subjected to magnetic stirring at 30° C. for 1.0 h, hydrothermal reaction at 90° C. for 12.0 h, and then cooled to obtain a precipitate;
[0049] (5) The precipitate obtained in step (4) is washed to neutrality, and then dried at 100°C to obtain a hydrotalcite precursor Ni 0.5 Co 0.5 Al1-LDH;
[0050] (6) The hydrotalcite precursor obtained in step (5) was calcined at 500° C. for 3.0 h in an air atmosphere to obtain a hydrotalcite oxide precursor Ni 0.5 Co 0.5 Al1-LDO;
[0051] (7) The hydrotalcite oxide precursor obtained in step (6) was reduced at 500 °C for 1.5 h under a H2 atmosphere to obtain a CoNi bimetallic catalyst, denoted as Ni 0.5 Co 0.5 Al1-LD. Example
[0052] A CH4 / CO2 low-temperature and high-efficiency dry reforming CoNi bimetallic catalyst, the preparation method is basically the same as that of Example 1, and the difference from Example 1 is that: in step (1), according to the molar ratio of cobalt nitrate, nickel nitrate and aluminum nitrate of 0.5:0.3:1, 0.7275g of cobalt nitrate, 0.4362g of nickel nitrate and 1.875g of aluminum nitrate are weighed; in step (2), according to [n(CO3 2- ) = 2n(Al 3+ )]、[n(OH - ) = 2[n(Co 2+ )+n(Ni 2+ )+n(Al 3+)], weigh 1.06g Na2CO3 and 0.72g NaOH, and dry them at constant temperature to obtain the hydrotalcite precursor Ni 0.3 Co 0.5 Al1-LDH, after calcination, obtains hydrotalcite-like oxide precursor Ni 0.3 Co 0.5 Al1-LDO, the final prepared catalyst is denoted as Ni 0.3 Co 0.5 Al1-LD. Example
[0053] A CH4 / CO2 low-temperature and high-efficiency dry reforming CoNi bimetallic catalyst, the preparation method is basically the same as that of Example 1, and the difference from Example 1 is that in step (1), the molar ratio of cobalt nitrate, nickel nitrate and aluminum nitrate is 0.5:1:1, 0.7275g of cobalt nitrate, 1.454g of nickel nitrate and 1.875g of aluminum nitrate are weighed, and in step (2), according to [n(CO3 2- ) = 2n(Al 3+ )]、[n(OH - ) = 2[n(Co 2+ )+n(Ni 2+ )+n(Al 3+ )], weigh 1.06g Na2CO3 and 1g NaOH, and dry them at constant temperature to obtain the hydrotalcite precursor Ni1Co 0.5 Al1-LDH, after calcination, obtains hydrotalcite-like oxide precursor Ni1Co 0.5 Al1-LDO, the final prepared catalyst is denoted as Ni1Co 0.5 Al1-LD.
[0054] Comparative Example
[0055] A CH4 / CO2 low-temperature and high-efficiency dry reforming CoNi bimetallic catalyst, the preparation method of which is basically the same as that of Example 1, except that: in step (1), 0.7275 g of cobalt nitrate and 1.875 g of aluminum nitrate are weighed according to a molar ratio of cobalt nitrate, nickel nitrate and aluminum nitrate of 0.5:0:1; in step (2), [n(CO3 2- ) = 2n(Al 3+ )]、[n(OH - ) = 2[n(Co 2 + )+n(Ni 2+ )+ n(Al 3+ )], weigh 1.06g Na2CO3 and 0.6g NaOH, and dry them at constant temperature to obtain the hydrotalcite precursor Co 0.5Al1-LDH, after calcination, obtains the hydrotalcite oxide precursor Co 0.5 Al1-LDO, the final catalyst prepared is denoted as Co 0.5 Al1-LD.
[0056] Figure 1 The catalyst precursor Ni prepared in Examples 1-3 and Comparative Examples of the present invention is 0.5 Co 0.5 Al1-LDO、Ni 0.3 Co 0.5 Al1-LDO、Ni1Co 0.5 Al1-LDO、Co 0.5 H2-TPR diagram of Al1-LDO. Figure 1 It can be seen that the catalyst precursor Ni prepared in Examples 1-3 0.5 Co 0.5 Al1-LDO、Ni 0.3 Co 0.5 Al1-LDO、Ni1Co 0.5 Compared with the catalyst precursor Co prepared in the comparative example, Al1-LDO 0.5 Al1-LDO has superior reducibility.
[0057] Figure 2 The catalyst precursor Ni prepared in Examples 1-3 and Comparative Examples of the present invention is 0.5 Co 0.5 Al1-LDH、Ni 0.3 Co 0.5 Al1-LDH、Ni1Co 0.5 Al1-LDH、Co 0.5 XRD pattern of Al1-LDH, Figure 3 The catalyst Ni prepared in Examples 1-3 and Comparative Examples of the present invention 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD、Ni1Co 0.5 Al1-LD, Co 0.5 XRD pattern of Al1-LD. Figure 2 It can be seen that the precursor samples of hydrotalcite-like layered structures were successfully prepared by the preparation methods of Examples 1-3. Figure 3 It can be seen that after the samples prepared in Examples 1-3 were calcined at 500°C and reduced with H2 to obtain the corresponding catalysts, the characteristic diffraction peaks of the hydrotalcite-like structure disappeared; the diffraction peaks of metal Ni and Co were detected, while the diffraction peaks of other compounds of the two (such as oxides, alloys) were not detected, indicating that the catalysts prepared in Examples 1-3 were effectively reduced.
[0058] Figure 4 The catalyst Ni prepared in Examples 1-3 and Comparative Examples of the present invention 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD、Ni1Co 0.5 Al1-LD, Co 0.5 TEM characterization test picture of Al1-LD. Figure 4 It can be seen that the catalysts prepared in Examples 1-3 present a highly dispersed two-dimensional nanosheet-like disordered stacking structure.
[0059] Figure 5 The catalyst Ni prepared in Examples 1-3 and Comparative Examples of the present invention 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD、Ni1Co 0.5 Al1-LD, Co 0.5 CO2-TPD diagram of Al1-LD. Figure 5 It can be seen that the CO2 adsorption performance of the catalysts prepared in Examples 1-3 is better than that of the catalyst in the comparative example.
[0060] Experimental example
[0061] The reaction performance of the catalyst samples prepared in all the examples and comparative examples was investigated. The reaction was carried out in a normal pressure microreactor. 30 mg of the oxide precursor was weighed and placed in a U-shaped quartz glass reaction tube. H2 was introduced at a flow rate of 20 mL / min. The sample was heated to 500°C at a rate of 10°C / min. After H2 reduction for 1.5 h, the H2 introduced into the sample tube was switched to the raw gas (33.2 vol% CH4, 30.2 vol% CO2 and 36.6 vol% Ar), and the reaction was continued at a reaction space velocity of 40,000 mL·gcat. -1 ·h -1 The CH4 / CO2 reforming performance was measured at 500-700°C. Data was collected every 50°C, and the tail gas after the reaction was passed into a gas chromatograph with TCD for online detection and analysis. The reaction results are shown in Tables 1 and 2.
[0062] Table 1 Comparison of CH4 conversion in CH4 / CO2 dry reforming reaction
[0063]
[0064] Table 2 Comparison of CO2 conversion in CH4 / CO2 dry reforming reaction
[0065]
[0066] It can be seen from Table 1 and Table 2 that at normal pressure and reaction temperature of 500-700 °C, the conversion rates of CH4 and CO2 in the CH4 / CO2 dry reforming reaction of the CoNi bimetallic catalysts prepared in Examples 1-3 of the present invention are higher than those of the CoNi bimetallic catalysts prepared in Comparative Example 4. 0.5 Al1-LD has basically improved significantly, among which Ni 0.5 Co 0.5 When Al1-LD is used as the catalyst, the conversion rates of CH4 and CO2 reach the highest in the temperature range of 500-700 °C, and are much higher than those of Comparative Example 4. 0.5 Co 0.5 As a catalyst for CH4 / CO2 dry reforming reaction, Al1-LD has a CH4 and CO2 conversion rate of 89.24% and 57.62%, respectively. At normal pressure and reaction temperature of 650℃, the CH4 and CO2 conversion rates are 85.71% and 52.71%, respectively, which are close to the equilibrium conversion rate of CH4 / CO2 dry reforming.
[0067] Figures 6 to 11 The Ni prepared in Examples 1-3 of the present invention are 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD and Ni1Co 0.5 The stability test diagram of CH4 / CO2 dry reforming of Al1-LD catalyst. It can be seen from the figure that the catalyst Ni prepared in Example 1-3 0.5 Co 0.5 Al1-LD、Ni 0.3 Co 0.5 Al1-LD and Ni1Co 0.5 After 10 cycles of testing, Al1-LD still did not show obvious deactivation and still maintained a relatively high CH4 / CO2 dry reforming catalytic performance, which proves that the catalyst of the present invention has relatively high activity and good stability in use.
[0068] The present invention has been disclosed above with preferred embodiments, but they are not intended to limit the present invention. Any technical solutions obtained by adopting equivalent replacement or equivalent transformation solutions fall within the protection scope of the present invention.
Claims
1. Application of CoNi bimetallic catalyst in CH4 / CO2 dry reforming reaction, characterized in that: The temperature of CH4 / CO2 dry reforming reaction is 650-700°C; the preparation method of the catalyst is: mixing cobalt nitrate, nickel nitrate and aluminum nitrate with distilled water to obtain a mixed metal salt solution; Dissolve Na2CO3 and NaOH in distilled water to obtain Na2CO3 solution and alkaline solution; Adding the mixed metal salt solution and the alkaline solution dropwise to the Na2CO3 solution simultaneously to obtain a mixed solution; The mixed solution is stirred and then subjected to a hydrothermal reaction to obtain a precipitate; The obtained precipitate is dried and then calcined in an air atmosphere to obtain a hydrotalcite-like oxide precursor; The hydrotalcite-like oxide precursor is reduced in a hydrogen atmosphere to obtain a CoNi bimetallic catalyst; Among them, the molar ratio of cobalt nitrate, nickel nitrate and aluminum nitrate is 0.5:0.3-1:1; the molar ratio of Na2CO3 to aluminum nitrate is 2:1, and the molar ratio of NaOH to the sum of cobalt nitrate, nickel nitrate and aluminum nitrate is 2:1; the calcination temperature in air atmosphere is 400-600°C, and the calcination time is 3.0h; the reduction temperature in hydrogen atmosphere is 400-600°C, and the reduction time is 1.0-2.0h.
2. The use of the CoNi bimetallic catalyst according to claim 1 in CH4 / CO2 dry reforming reaction, characterized in that: The stirring temperature of the mixed solution is 30-60°C, and the stirring time is 1.0-3.0h.
3. The use of the CoNi bimetallic catalyst according to claim 1 in CH4 / CO2 dry reforming reaction, characterized in that: One or more of the following conditions are met: The temperature of the hydrothermal reaction is 90 to 120°C, and the time of the hydrothermal reaction is 10.0 to 24.0 hours; The drying temperature of the obtained precipitate is 60-120°C.